(untitled) (Damascus University Journal for engineering sciences, 2022)
After choosing The appropriate dimensions for the Diffuser and Computer designing it, in this paper we performed computer simulation on this diffuser, with and without brim, using CFD ANSYS program, taking into consideration an accurate resolution algorithm, equivalent to 100 cycles to raise the accuracy of the results, with the aim of knowing the aerodynamic behavior of the wind within this diffuser, the amount of increase in wind speed that we can obtain by using diffuser, and the effect of brim at the end of this diffuser on this increase, compared to a diffuser having the same dimensions without brim. In this paper the simulation results and their analysis will be presented, at three different wind speed (3,6,8m/s).